Signalling servant leadership: How followers interpret leader behaviours - Eva, Nathan; Hunter, Emily M.; Neubert, Mitchell J.; Wood, Matthew (Journal of Management Studies, 2026)
Based on over 25 years of studies on servant leadership and multiple meta‐analyses, we can safely say servant leadership positively affects individuals, teams, and organizations. Yet to reap these benefits, followers need to recognize leaders' behaviours as servant leadership. Because serving others requires time and energy, leaders may bear the costs of servant leadership without generating its benefits when those efforts go unrecognized. To address this concern, we draw on signalling theory to examine how leaders convey servant‐oriented intentions through observable, costly behaviours. We test our hypotheses across three experiments, two conjoint analyses and one between‐subjects video‐based study to examine how followers interpret multiple leader and organizational signals. Our findings help explain the behaviour–perception mechanism through which leaders come to be recognized as servant leaders, while highlighting the complexities leaders face in signalling their intentions to followers. We show that leaders signal servant leadership through observable, costly service‐oriented behaviours, such as helping followers grow and succeed, and need to engage in these behaviours frequently and consistently. We further show that the efficacy of these signals depends on followers' levels of prosocial motivation and the signalling environment in which the leader operates, providing evidence of how followers interpret multiple signals.